2011
DOI: 10.1074/jbc.m110.205088
|View full text |Cite
|
Sign up to set email alerts
|

Creating Directed Double-strand Breaks with the Ref Protein

Abstract: The bacterial recombinase, RecA protein, plays a central role in maintenance of genome stability. It generally functions as a RecA nucleoprotein filament formed on DNA (1). RecA has three identified functions in the cell. First, it participates directly in all recombination processes. Filaments of Escherichia coli RecA protein form most readily on ssDNA; these filaments can then catalyze DNA pairing and strand exchange with a homologous duplex DNA (2). A RecA filament complexed with an oligonucleotide can inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 63 publications
(35 reference statements)
2
49
0
Order By: Relevance
“…In all figures, unless otherwise noted, the variant RecA E38K was used in place of WT RecA. We have previously demonstrated that RecA E38K enhances the RecA-dependent-targeted DSB activity of Ref beyond that of WT RecA (1)
Figure 1.Ref creates targeted DSBs in cdsDNA through a nicked intermediate. ( A ) The reaction scheme is shown.
…”
Section: Resultsmentioning
confidence: 99%
“…In all figures, unless otherwise noted, the variant RecA E38K was used in place of WT RecA. We have previously demonstrated that RecA E38K enhances the RecA-dependent-targeted DSB activity of Ref beyond that of WT RecA (1)
Figure 1.Ref creates targeted DSBs in cdsDNA through a nicked intermediate. ( A ) The reaction scheme is shown.
…”
Section: Resultsmentioning
confidence: 99%
“…We note that SSPRO8 Figure 2. % coil content vs order counter for sampled molecules, 3PLW 90 (b) 2R6V 91 (c) 1DZF 92 (d) 3HZ8 93 (e) 3UMH 94 . The five proteins are ordered from greatest to least coil content.…”
Section: Resultsmentioning
confidence: 99%
“…We again observe key regions of poor 2D-CNN confidence or inaccuracy and low molecular longevity that do not have a corresponding disorder Figure 6. Models of the five sampled proteins in this study: (i) 3PLW 90 (ii) 2R6V 91 (iii) 1DZF 92 (iv) 3HZ8 93 (v) 3UMH 94 . (a) Molecular longevity on a red/blue scale for low/high structural longevity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An effort to characterize the bacteriophage P1 Ref protein as a suspected RecA-regulator protein revealed that Ref is actually a RecA-dependent, HNH-family endonuclease ( 7 ). Ref has the novel property of only cleaving DNA to which RecA protein is bound.…”
Section: Introductionmentioning
confidence: 99%